Wood Quality of Clones Teak with Different Planting Distance - Andi D Yunianti; Imam Wahyudi; Iskandar Z Siregar; Gustan Pari (Masyarakat Peneliti Kayu Indonesia, 2011)
Many researchs have been done focusing on the wood quality of teak (Tectona grandis L.f.) especially at the various age level and different locations. This research analyzed different planting distance : (3 x 3) m2 and (2 x 6) m2 from 2 clones; Cepu and Madiun cloned. Oven-dried density, fiber dimension, microfibril angle and modulus of elasticity were determined to asses the wood quality. The results showed that the wood quality of teak from spacing (3 x 3) m2 were better than (2 x 6) m2, although diameter and growth rate were higher in spacing (2 x 6) m2. However, there were not diffrences of wood quality for both clones.Key words : Cepu clone, Madiun clone, planting distance, Tectona grandis, wood quality.